Pendidikan puasa dalam perpektif pendekatan transmisi: Menggali pengalaman siswa sekolah menengah atas - Salsabila, Shavira; Fakhruddin, Agus; Firmansyah, Mokh. Iman (International Journal of Nusantara Islam, 2025)
The purpose of this study was to explore high school students' views on fasting and their experiences in receiving fasting education, using a transmission pedagogic perspective. This study used a qualitative approach with a phenomenological design and successfully explored 139 students' experiences through questionnaires. The collected data were analyzed with the help of NVivo 12 software, which facilitated the data tabulation process. The data analysis process was carried out through three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that students get information about fasting and its values, but they only believe the information conveyed by credible subjects, who are able to practice fasting well and become role models for them. Environmental conditioning with structured fasting education programs, reinforced by harmonious collaboration between religious teachers, parents, and religious preachers, provides opportunities for students to gain insight into fasting as well as opportunities to practice the practice of fasting. In addition, the reinforcement received by students further boosts their motivation to fast. However, the influence of the peer environment, social media, and the lack of role models in daily life reduce students' intrinsic motivation and hinder the consistency of their character in carrying out the practice of fasting continuously.